What do you say after you say hello? the psychology of human destiny - "Berne, Eric" (London, 1975)
What Do You Say After You Say Hello? explains what makes the winners win, the losers lose, and the in-betweens so boring... In it, Dr Eric Berne reveals how everyone's life follows a predetermined script - a script they compose for themselves during early childhood. The script may be a sad one, it may be a successful one; it decides how a person will relate to his colleagues, what sort of person he will marry, how many children he will have, and even what sort of bed he will die in... What Do You Say After You Say Hello? demonstrates how each life script gets written, how it works and, more important, how anyone can improvise or change his script to make a happy ending...
Keywords: Personal improvement